2010
DOI: 10.1038/eye.2010.34
|View full text |Cite
|
Sign up to set email alerts
|

Is cataract associated with cardiovascular morbidity?

Abstract: Aims To evaluate the prevalence of cardiovascular disease (CVD) and its risk factors among patients undergoing cataract surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 29 publications
(35 reference statements)
1
28
0
Order By: Relevance
“…23 It is known that preoperative risk stratification with myocardial perfusion imaging provides an incremental prognostic value in intermediate-risk surgery, but not in low-risk operations. 24 We believe that the association between clinical comorbidities and cataractogenesis, 25 fear of cancellation of surgery, institutional requirements and medicolegal concerns may have contributed to the present results regarding the ordering of preoperative tests. 26 Hypertension, a minor outcome, was the most common adverse event in the current study.…”
Section: Discussionmentioning
confidence: 84%
“…23 It is known that preoperative risk stratification with myocardial perfusion imaging provides an incremental prognostic value in intermediate-risk surgery, but not in low-risk operations. 24 We believe that the association between clinical comorbidities and cataractogenesis, 25 fear of cancellation of surgery, institutional requirements and medicolegal concerns may have contributed to the present results regarding the ordering of preoperative tests. 26 Hypertension, a minor outcome, was the most common adverse event in the current study.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies have shown that age-related cataract is associated with systemic comorbidities [42] and general functional decline [43] in older adults. We confirmed that these systemic comorbidities and functional decline are sufficient to cause death in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Another potential explanation for the association between age-related cataract and decreased survival is that age-related cataract may be a biomarker of frailty and ageing. Previous studies have reported the significant relationship between age-related cataract and comorbidities, such as atherosclerosis (Nemet et al 2010) chronic kidney disease (Wang et al 2012;Wong et al 2016) and osteoporosis (Huang et al 2018). It has been indicated that age-related cataract and systemic comorbidities may share similar underlying pathogenesis, such as oxidative stress and atherosclerosis.…”
Section: E330mentioning
confidence: 99%